Illusionism : as a theory of consciousness. - Frankish, Keith (Andrews UK, 2017)
Illusionism is the view that phenomenal consciousness (in the philosophers' sense) is an illusion. This book is a reprint of a special issue of the Journal of Consciousness Studies devoted to this topic. It takes the form of a target paper by the editor, followed by commentaries from various thinkers, including leading defenders of the theory such as Daniel Dennett, Nicholas Humphrey, Derk Pereboom and Georges Rey. A number of disciplines are represented and different viewpoints are discussed and defended. The colleciton is tied together with a response to the commentaries from the editor.